A Novel Frequency Domain Visible Light Communication (Vlc) Three-Dimensional Trilateration System for Localization in Underground Mining - Soto-Gomez, J; Seguel-Gonzalez, F (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
[No abstract available]